2021
DOI: 10.1016/j.jcjp.2021.100022
|View full text |Cite
|
Sign up to set email alerts
|

The need for a standardized whole leg radiograph guideline: The effects of knee flexion, leg rotation, and X-ray beam height

Abstract: Introduction: Lower limb malalignment is a major risk factor for knee osteoarthritis (OA) and is mainly diagnosed using the Hip Knee Ankle Angle (HKA). Therefore, accurate HKA measurements are indispensable. Objectives: This study aimed to research the effects of knee flexion, leg rotation, and X-ray beam height on the accuracy of the HKA measurement. To convert our findings into a guideline for obtaining whole leg radiographs (WLR) in favor of accuracy and reproducibility. Methods: An in vitro experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Knee flexion was also only indirectly controlled in our protocol by asking patients to stand in full knee extension. Previous studies have demonstrated that a substantial degree of leg rotation of 10° or more is needed to alter HKA measurements in a clinically relevant fashion 8,18,34,35 . But with added knee flexion of 10°, the error becomes at least 2°3 5,36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Knee flexion was also only indirectly controlled in our protocol by asking patients to stand in full knee extension. Previous studies have demonstrated that a substantial degree of leg rotation of 10° or more is needed to alter HKA measurements in a clinically relevant fashion 8,18,34,35 . But with added knee flexion of 10°, the error becomes at least 2°3 5,36 .…”
Section: Discussionmentioning
confidence: 99%
“…A potential clinically relevant problem when considering that up to one-third of knee OA patients presents a knee flexion contracture of 6° or greater 37 . This highlights the importance of controlling leg rotation during WLR acquisition, to minimize the effect of knee flexion on standing WLRs 35,36 . Of note, controlling leg rotation using fixed floor template is not suitable for every patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Included patients were all placed in the examination room following the WLR protocol used at our radiology department. 10 The conditions for obtaining the digital photograph were kept similar to the WLR, making the images from the 2 modalities consistent for assessments. The patient’s feet were placed 10° externally rotated and 10 cm apart on a template.…”
Section: Methodsmentioning
confidence: 99%